2013
DOI: 10.1111/cei.12198
|View full text |Cite
|
Sign up to set email alerts
|

Possible pathogenic role of T helper type 9 cells and interleukin (IL)-9 in atopic dermatitis

Abstract: SummaryT helper type 9 (Th9) cells are a novel identified subset of CD4 + T helper cells, which could partly contribute to allergic inflammation, while the precise contribution of Th9 cells in atopic dermatitis (AD) remains unknown. We aimed to explore the possible role of Th9 cells in AD pathogenesis. The Th9 cell percentage, transcription factor PU.1 and cytokine interleukin (IL)-9 mRNA levels, as well as IL-9 serum concentration in peripheral circulation, were measured in AD patients, psoriasis patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 31 publications
7
87
1
6
Order By: Relevance
“…Recent studies revealed a T-cell subset (Th9 cells) that predominantly produces IL-9 and is distinct from the classic Th1, Th2 and Th17 subsets (2-4). Several reports showed that Th9 cells could be involved in the pathogenesis of chronic allergic disorders such as asthma, allergic rhinitis and atopic dermatitis (23,24). Further studies indicated that serum levels of IL-9 are increased in patients with SLE and other autoimmune diseases such as systemic scleroderma (8,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed a T-cell subset (Th9 cells) that predominantly produces IL-9 and is distinct from the classic Th1, Th2 and Th17 subsets (2-4). Several reports showed that Th9 cells could be involved in the pathogenesis of chronic allergic disorders such as asthma, allergic rhinitis and atopic dermatitis (23,24). Further studies indicated that serum levels of IL-9 are increased in patients with SLE and other autoimmune diseases such as systemic scleroderma (8,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Data from Ma et al show no significant difference of IL-9 production between simple AD patients and AD patients with allergic rhinitis or asthma, and IL-9 can promote the secretion of VEGF by keratinocytes in a time-and dose-dependent manner, indicating that the pathogenesis of AD may be mediated by the increased release of VEGF by keratinocyes after IL-9 stimulation [44].…”
Section: Atopic Dermatitis (Ad)mentioning
confidence: 97%
“…Three groups have reported that IL-9 expression increases in AD patients compared with control group [4,11,44], demonstrating the essential role of IL-9 in AD, an inflammatory disorder of the skin characterized by an impaired immune response. Data from Ma et al show no significant difference of IL-9 production between simple AD patients and AD patients with allergic rhinitis or asthma, and IL-9 can promote the secretion of VEGF by keratinocytes in a time-and dose-dependent manner, indicating that the pathogenesis of AD may be mediated by the increased release of VEGF by keratinocyes after IL-9 stimulation [44].…”
Section: Atopic Dermatitis (Ad)mentioning
confidence: 99%
“…Une étude récente a montré une augmentation significative du nombre de cellules Th9 dans le sang de patients atteints de dermatite atopique [19,44] (➜). Les Th9 semblent également être impliqués dans la maladie asthmatique.…”
Section: Maladies Allergiquesunclassified